2016
DOI: 10.1007/s12192-016-0666-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of aspirin-induced HspB1 against heat stress damage in chicken myocardial cells

Abstract: To understand the potential association of heat stress resistance with HspB1 induction by aspirin (ASA) in chicken myocardial cells, variations of HspB1 expression and heat stressed-induced damage of myocardial cells after ASA administration were studied in primary cultured myocardial cells. Cytopathological lesions as well as damage-related enzymes, such as creatine kinase-MB (CK-MB) and lactate dehydrogenase (LDH), indicated the considerable protective ability of ASA pre-treatment against acute heat stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…According to a series of markers for injury evaluation, aspirininduced HS resistance, which has been reported before (Wu et al 2015(Wu et al , 2016, was also observed in this study. Similar to the former studies, aspirin pretreatment inhibited the increased levels of the myocardial cell damage-related enzymes CK-MB and LDH and the pathological changes.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…According to a series of markers for injury evaluation, aspirininduced HS resistance, which has been reported before (Wu et al 2015(Wu et al , 2016, was also observed in this study. Similar to the former studies, aspirin pretreatment inhibited the increased levels of the myocardial cell damage-related enzymes CK-MB and LDH and the pathological changes.…”
Section: Discussionsupporting
confidence: 76%
“…Cell culture and stress model Primary cultures of chicken myocardial cells (provided by Shanghai Fu Meng Biological Technology Ltd, Shanghai, China) were cultured as we described before (Wu et al 2016). Cells were cultured (37°C and 5 % CO 2 ) on the Petri dishes for 72 h until the fusion rate was higher than 90 %.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations